A spanning approach to the acquisition of double definiteness in Norwegian - Anderssen, Merete (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This study demonstrates how lexical spanning can be used to explain the various stages in the acquisition of double definiteness in Norwegian. The approach takes syntactic terminals to consist of sub-morphemic elements that are lexicalised by words or morphemes. Work on Scandinavian DPs has demonstrated that they involve two determiner-‐‑like projections. Within the spanning approach, simple, unmodified structures in Norwegian are distinguished from modified ones by the fact that one morpheme spans both projections in the first case, while two morphological exponents are required to spell them out separately in the second. Furthermore, it has been argued that the term double definiteness is a misnomer, and that the two determiners spell out separate subcomponents of definiteness, Uniqueness and Specificity. For developmental reasons, Norwegian children start out by lexicalising these features individually. The suffixal article spells out Specificity, while a phonologically zero determiner spells out Uniqueness. When adjectives are introduced into this grammar, the result is a system that only spells out the suffixal article overtly, that is, an Icelandic type system. This development is followed by a period with a great deal of instability as the grammar tries to determine how to lexicalise the various terminals in the determiner phrase.